Parametric study of hydrogen production via sorption enhanced steam methane reforming in a circulating fluidized bed riser. (31st December 2018) - Phuakpunk, Kiattikhoon; Chalermsinsuwan, Benjapon; Putivisutisak, Sompong; Assabumrungrat, Suttichai
Highlights: Kinetics of steam methane reforming and carbonation were incorporated in CFD model. 2 k factorial design was used to analyze parameters. Hydrogen purity could reach equilibrium as well as that conducted in bubbling bed. Gas velocity, riser diameter and solid flux had major effects on system designing. Abstract: Computational fluid dynamics was applied for sorption enhanced steam methane reforming (SESMR) operating in a circulating fluidized bed (CFB) riser. The solid mixtures consisted of Ni-based catalyst and CaO sorbent. The aim of study was to design a proper pilot-scale CFB riser which produced hydrogen (H2 ) with both high purity and high flux. The design parameters and the reaction parameters were examined with 2 k full factorial design. The significances of each parameter were analyzed by analysis of variance. Using the optimum result, the highest H2 purity reached 98.58% in dry basis accompanied with the highest H2 flux of 0.301 kg/m 2 s. The hydrodynamics of this optimum case showed that SESMR was nearly completed since 5.0 m height because axial and radial distributions of solid were well developed without excessive segregation between catalyst and sorbent. Thus, the H2 purity and the H2 flux approached fully developed within the riser height.